Inhibition of microRNA‐149 protects against recurrent miscarriage through upregulating RUNX2 and activation of the PTEN/Akt signaling pathway. Issue 12 (16th September 2020) - Wang, Peng; Chen, Xu; Chang, Ying; Wang, Yanping; Xu, Xinran; Guo, Yuling; Cui, Hongyan
Abstract: Aim: Recently, microRNA‐149 (miR‐149) has been indicated to act as an oncogene or a tumor suppressor in various malignant tumors, while its inner mechanisms in recurrent miscarriage (RM) are still in infancy. Therein, this study intends to decode the mechanism of miR‐149 in RM. Methods: miR‐149 and RUNX2 expression in the chorionic tissues of normal pregnant women and RM patients were first examined, and the correlation between miR‐149 and RUNX2 was analyzed. Subsequently, miR‐149 was upregulated in HTR‐8 cells or downregulated in BEWO cells, and then the changes in biological functions of trophoblasts in RM were detected. Furthermore, the expression of PTEN/Akt signaling pathway‐related factors in trophoblasts was detected by western blot analysis. Results: miR‐149 expression was increased while RUNX2 expression was suppressed in RM patients, and miR‐149 was negatively correlated with RUNX2. Overexpressed miR‐149 induced cell apoptosis and inhibited cell activity, while reduced miR‐149 in trophoblasts contributed to opposite experimental results. Moreover, miR‐149 promoted the expression of PTEN and inhibited Akt phosphorylation by targeting RUNX2, thereby inhibiting trophoblast activity and promoting their apoptosis. Conclusion: Our study demonstrates that miR‐149 knockdown halted the RM development through upregulating RUNX2 and activation of the PTEN/Akt signaling pathway.